On the Problem of Social Dependence of Individual Consciousness - Lazauskas, Justinas (Problemos, 1969)
The author points out in the first place cognitive and social aspects of this problem. Social dependence of individual consciousness is a complicated process of interaction between an individual as a member of society and social medium. In the paper special attention is given to the activity of consciousness: to the interrelation of reflection and reproduction of reality, to the process of transition of the material into the ideal and, vice versa, in man’s working activity.